2021
DOI: 10.3390/app11030964
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Hydrolysis of Sewage Sludge: A Case Study of a WWTP in Burgos, Spain

Abstract: An evaluation of the energy and economic performance of thermal hydrolysis technologies is carried out on a theoretical basis. The wastewater treatment plant (WWTP) of Burgos (Spain) was the base scenario of this evaluation. Energy and mass balances were established considering the registered data of primary and secondary thickened sludge in the WWTP for 2011 to 2016. These balances were analysed considering five different scenarios, taking as Scenario 1, the plant operating with conventional mesophilic digest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
0
8
0
1
Order By: Relevance
“…The different technologies available for increasing biogas yields include pre-treatments to facilitate the hydrolysis of particulate material to allow easy access to anaerobic microflora. However, some technologies may increase the facility's energy demand and negatively affect installation costs [156]. The thermal hydrolysis process is fully developed at the industrial level and allows the enhancement in biogas production along with a significant decrease in the volume of sludge [157].…”
mentioning
confidence: 99%
“…The different technologies available for increasing biogas yields include pre-treatments to facilitate the hydrolysis of particulate material to allow easy access to anaerobic microflora. However, some technologies may increase the facility's energy demand and negatively affect installation costs [156]. The thermal hydrolysis process is fully developed at the industrial level and allows the enhancement in biogas production along with a significant decrease in the volume of sludge [157].…”
mentioning
confidence: 99%
“…Different thermal hydrolysis technologies were analyzed using data from the wastewater treatment plant of Burgos (Spain) as the base scenario when operating with conventional mesophilic anaerobic digestion [13]. García-Cascallana et al [13] showed that when hydrolysis was applied to digested sludge and sludge from the Solidstream ® process, this resulted in a 35% increase in biogas available for engines and a 23% increase in electricity production. In this case, the main advantage of the hydrolysis process is the decrease in the volume of digesters and the amount of dewatered sludge needing final disposal [13].…”
Section: Strategies To Improve Anaerobic Digestion Of Organic Wastementioning
confidence: 99%
“…García-Cascallana et al [13] showed that when hydrolysis was applied to digested sludge and sludge from the Solidstream ® process, this resulted in a 35% increase in biogas available for engines and a 23% increase in electricity production. In this case, the main advantage of the hydrolysis process is the decrease in the volume of digesters and the amount of dewatered sludge needing final disposal [13].…”
Section: Strategies To Improve Anaerobic Digestion Of Organic Wastementioning
confidence: 99%
“…Two thermal hydrolysis reactors with a working volume of 5.1 m 3 operating under batch conditions (3 cycles each) would be needed. Based on technical data reported by García-Cascallana et al [27], a steam injection time of 15 min was assumed with a 20 min duration for the hydrolysis process. Using these assumptions, the steam flow needed would account for 3750 kg/h for a total period of 1.5 h (derived from the summation of the six operating cycles).…”
Section: Scenariomentioning
confidence: 99%
“…Other benefits should also be added regarding the safety of the product and improvements in the rheological properties of digestate (lower viscosity and improved dewaterability) [19,25]. Other studies focus on energy evaluations dealing with global process performance, indicating that the energy demand of the additional equipment associated with the thermal hydrolysis unit may be higher than the energy derived from digestion enhancement [26,27]. This disadvantage may be offset by a much lower amount of sludge needing final disposal [28], along with a lower volume of reactor required to treat the pre-treated sludge.…”
Section: Introductionmentioning
confidence: 99%